Convergence of local prices in Mexico: A pairwise approach - Rodríguez Benavides, Domingo; Rodríguez Nava, Abigail (Estudios Económicos de El Colegio de México, 2019)
We analyze the convergence of local price levels in Mexico through a pairwise approach. For this purpose, we apply unit root tests to the relative prices of all possible combinations of cities and different goods and services. One of the main advantages of this approach is that a city of reference is not chosen as the basis for relative price levels in the analysis of stationarity. The approach is applied to monthly series of general and disaggregated indexes of a sample of prices of goods and services in the period 1982-2016. The results allow to reject the null hypothesis of non-convergence between the relative prices for most of the analyzed goods and services of the cities considered, although the convergence is to some extent limited.